Dissolution kinetics of monazite LnPO4 (Ln = La to Gd): A multiparametric study. (June 2018) - Gausse, Clémence; Szenknect, Stéphanie; Mesbah, Adel; Clavier, Nicolas; Neumeier, Stefan; Dacheux, Nicolas
Abstract: The chemical durability of monazites LnPO4 (Ln = La → Gd) was investigated. The influence of several parameters on the normalized dissolution rates, including acidity and temperature, was investigated under dynamic conditions. The impact of the saturation processes of the solution was also examined through static experiments. Under the investigated conditions, the normalized dissolution rates were found to be very low for all the lanthanide elements considered (La → Gd). The partial order of the dissolution reaction related to the proton activity varied from 0.7 ± 0.2 to 1.5 ± 0.3 for LnPO4 (Ln = La, Ce, Nd and Gd). The apparent range of activation energies associated with the dissolution of monazites E app shifted from 54 to 103 kJ mol −1 below 313 K (characteristic values for dissolution process controlled by surface reactions) to 6–17 kJ mol −1 between 313 K and 363 K. These values are usually associated with mass transport as the rate-limiting step in the dissolution mechanism. This modification suggested an impact of the f (ΔR G ) term included in the multiparametric expression for the normalized dissolution rate. Indeed, the Gibbs energy of the dissolution reaction, ΔR G, increased from 298 K to 363 K with a significant break at 313 K. This result indicated that the solutions approached thermodynamic equilibrium with respect to rhabdophane in experiments performed above 313 K. This could impact the normalized dissolution rates, and thus, the parameters associated with kinetics. The study on the long-term behavior of NdPO4 under static conditions (298 K, 0.1 M HNO3 ) confirmed this point. After 10 days of leaching, the normalized dissolution rate decreased by more than one decade, whereas the saturation index with respect to rhabdophane increased significantly. This strong decrease in the normalized dissolution rate suggests that the saturation index in the solution impacts the normalized dissolution rates, even for solutions that were macroscopically under-saturated with respect to the rhabdophane. Graphical abstract: Image 1 Highlights: The chemical durability of monazites LnPO4 (Ln = La .→ Gd) was investigated. The influence of several parameters was determined far from equilibrium. The dependence of the rate with the Gibbs free energy of reaction was evidenced. The precipitation of rhabdophane LnPO4 ·0.667H2 O was suspected. Monazites appeared as a durable radwaste matrix.